Fodder conservation for round the year availability through bag silage - Kansal, S K; Singh, Jaswinder; Hundal, J S (Indian Farming, 2022)
The unemployed youth/landless farmers can be engaged to prepare the bag silage as an enterprise in their area for their livelihood concerns.